Anxiety, depression, resilience and self-esteem in individuals with cardiovascular diseases - Isabela Gonzales Carvalho; Eduarda dos Santos Bertolli; Luciana Paiva; Lidia Aparecida Rossi; Rosana Aparecida Spadoti Dantas; Daniele Alcalá Pompeo
ABSTRACT Objectives: to analyze the relationship between anxiety and depression symptoms, resilience and self-esteem with sociodemographic and clinical characteristics; correlate resilience and self-esteem with age and duration of the disease; check associations between anxiety and depression with measures of resilience and self-esteem among individuals with cardiovascular diseases. Method: correlational study conducted in a large university hospital in the interior of the state of São Paulo, Brazil. The population was composed of adult inpatients with cardiovascular diseases. A non-probabilistic consecutive sample was composed of 120 patients. Variables of interest were assessed using the Hospital Anxiety and Depression Scale, Resilience Scale, and Rosenberg Self-Esteem Scale. Results: anxiety and depression symptoms were present in 32.5% and 17.5% of the patients, respectively, and were associated with the female sex (p = 0.002; p = 0.022). Manifestations of depression were associated with the presence of comorbidities (p = 0.020). More resilient patients did not present depression symptoms (p < 0.001) and anxious women were more resilient (p = 0.042). The highest scores regarding self-esteem were present in patients with anxiety and depression. Men presented higher resilience and lower self-esteem compared to women. Conclusion: patients with anxiety and depression were less resilient but presented higher self-esteem.